Delaying tackling in youth contact sports: Moving toward a safer future or softening the game? - Garrett, J. M.; Headrick, J. (Sports Medicine, 2025)
This current opinion article evaluates the rationale for delaying or modifying tackling in youth contact sports until age 12 years. There is growing concern that young athletes may be at heightened risk of sports-related concussions (SRC) and other injuries due to their developing brains and less-developed neuromuscular control. Recent studies exploring non-tackle formats, weight categories and body-checking restrictions demonstrate the potential benefits of reducing high-impact collisions at younger ages without the detrimental effects, i.e., increased SRC rate, when contact is introduced. Yet, critics may worry that delayed contact, such as tackling, may leave children unprepared for physical challenges, dampen sports engagement or fail to yield significant benefits in the long term. This article synthesises emerging evidence, highlights controversies and proposes future directions for policies and research. Ultimately, delaying tackling until the age of 12 years, paired with robust contact skill instruction and progression, may offer a safer path for children`s long-term health and sports participation.